Características socioeconómicas y la experiencia de caries en niños/niñas del pueblo indígena Yanacona (Pitalito-Huila) (2023)
describe the socioeconomic characteristics and the experience of caries in a population of children from five to twelve years of age from the Yanakona ethnic group of the Intillagta Hijos del Sol indigenous reservation of Pitalito Huila.